Incidence of Uveitis in Secukinumab‐treated Patients With Ankylosing Spondylitis: Pooled Data Analysis From Three Phase 3 Studies. Issue 5 (30th April 2020) - Deodhar, Atul A.; Miceli‐Richard, Corine; Baraliakos, Xenofon; Marzo‐Ortega, Helena; Gladman, Dafna D.; Blanco, Ricardo; Das Gupta, Ayan; Martin, Ruvie; Safi, Jorge; Porter, Brian; Shete, Abhijit; Rosenbaum, James T.
Abstract : Objective: The objective of this study was to report the incidence of uveitis in secukinumab‐treated patients with ankylosing spondylitis (AS) in a pooled analysis of three phase 3 trials (MEASURE 1‐3 [ClinicalTrials.gov identifiers NCT01358175, NCT01649375, NCT02008916]). Methods: Analysis included pooled patient‐level data from all patients (N = 794) who received any dose (one or more) of secukinumab up to the last patient attending the week 156 study visit in MEASURE 1 and up to the week 156 visit in MEASURE 2 and the week 104 visit in MEASURE 3 for each patient. Postmarketing data were from the periodic safety update report. Incidence of uveitis is reported as the exposure‐adjusted incidence rate (EAIR) per 100 patient‐years of secukinumab exposure. Results: Overall, 135 (17%) patients reported preexisting (but not active or ongoing) uveitis at baseline, and 589 (74.2%) patients were HLA antigen B27 positive. The EAIR for uveitis was 1.4 per 100 patient‐years over the entire treatment period. Among all cases of uveitis (n = 26), 14 (54%) were flares. The exposure‐adjusted reporting rate of uveitis in the postmarketing data (which included patients across the three approved indications of psoriasis, psoriatic arthritis, and AS) was 0.03 per 100 patient‐years based on cumulative secukinumab exposure of 96 054 patient‐years. Conclusion: The incidence rate of uveitis in secukinumab‐treated patients with active AS does not suggest an increased risk with secukinumab treatment.